Thought Leadership in Advancing International Business Research - Lewin, Arie Y.; Cavusgil, S. Tamer; Hult, G. Tomas M.; Griffith, David A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
This volume is devoted to those areas that can advance our understanding of international business. It contains contributions from intellectual leaders of the field, using cutting edge research to explore frontier topics in international business, and to look at where international business is going.
Keywords: International business enterprises; International economics; International Business; International Economics